Meat and vegetable semi-finished products with high content of minerals - Haschuk, Olexandra; Moskaluyk, Oksana; Budarina, Elizaveta; Linichenko, Andrii (My University, 2023)
З метою позитивного впливу на харчування населення України є використання продуктів з підвищеним мікроелементним складом. Розробка м'ясо-рослинних напівфабрикатів збагачених мінеральними речовинами за рахунок використання в рецептурах рослинної сировини дає змогу збагатити раціон населення функціональними продуктами. In order to have a positive effect on the nutrition of the population of Ukraine, it is necessary to use products with an increased trace element composition. The development of meat-vegetable semi-finished products enriched with mineral substances due to the use of plant raw materials in recipes makes it possible to enrich the diet of the population with functional products.
Keywords: м'ясо-рослинні напівфабрикати із м'яса курячого; яловичини; рослинна сировина; meat and vegetable semi-finished products from chicken; beef; vegetable raw materials; кафедра технології м’яса і м’ясних продуктів